An Analysis of Students’ Ability and Difficulties in Writing Skills at SMAN 12 Sinjai - Haera, Ulfa; Ariyani, Amra; Asriati, Asriati (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research aims to determine students' ability and difficulties in writing skills. In this study, the research instruments used are writing test and interviews, and used a mixed method. In this research, class 12 from SMAN 12 Sinjai was selected as the population, and class 12.3 was chosen as the research sample. The sampling in this study used a cluster random sampling technique to carry out a writing test, especially in procedure text, and a purposive sampling technique to carry out interviews. The writing test results were analyzed quantitatively using Microsoft Excel and the interview were analyzed qualitatively. The results of data analysis show that 58% of students were in the “very poor” category, 23% got a score categorized as “good” category, 12 % students in the “fair” category, and there is only 7% in the poor category. From the writing test, students can better master the organization and content components and the students experience difficulties ranging from vocabulary, grammar, mechanics, organization, and content. In conclusion, students’ writing ability is a “very poor” category, and they have difficulties in writing skills in components of writing.Keywords-Writing Ability, Students’ Difficulties in Writing.